2020
DOI: 10.3847/1538-4357/ab8c46
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Pair Producing Gaps in Black Hole Magnetospheres. II. General Relativity

Abstract: This is the second paper in a series where we examine the physics of pair producing gaps in low-luminosity accreting supermassive black hole systems. In this paper, we carry out time-dependent self-consistent fully general relativistic 1D particle-in-cell simulations of the gap, including full inverse Compton scattering and photon tracking. Similar to the previous paper, we find a highly time-dependent solution where a macroscopic vacuum gap can open quasiperiodically, producing bursts of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
5
29
1
Order By: Relevance
“…They modeled a black hole immersed in an initially vertical magnetic field, but used a simplified treatment for plasma supply that could only mimic how an electromagnetic cascade develops. This was improved upon in Levinson & Cerutti (2018), Yuan (2020), andCrinquand et al (2020), where a self-consistent treatment of inverse Compton (IC) scattering and pair production was implemented. In Crinquand et al (2020, hereafter C20), we simulated a monopole magnetosphere to capture the intrinsic activity of spark gaps, and showed that the BZ process could be successfully activated, as the magnetosphere was filled with pair plasma produced in the ergosphere.…”
Section: Introductionmentioning
confidence: 99%
“…They modeled a black hole immersed in an initially vertical magnetic field, but used a simplified treatment for plasma supply that could only mimic how an electromagnetic cascade develops. This was improved upon in Levinson & Cerutti (2018), Yuan (2020), andCrinquand et al (2020), where a self-consistent treatment of inverse Compton (IC) scattering and pair production was implemented. In Crinquand et al (2020, hereafter C20), we simulated a monopole magnetosphere to capture the intrinsic activity of spark gaps, and showed that the BZ process could be successfully activated, as the magnetosphere was filled with pair plasma produced in the ergosphere.…”
Section: Introductionmentioning
confidence: 99%
“…in the direction of the magnetic field), and propagate along a beam that is well collimated to an opening angle ≈ φ. During the propagation away from the gap, the seed electrons still encounter the ADAF photon field, and a post-gap cascade (Broderick & Tchekhovskoy 2015;Chen & Yuan 2020) occurs and increases the number of electrons by repeated curvature-radiation and IC emission and PP events. This post-gap cascade ceases when curvatureradiation emission becomes negligible and when IC scattering and PP can no longer be sustained by ADAF photons.…”
Section: Specification Of the Modelled Settingmentioning
confidence: 99%
“…It was also found that gaps form around the divide of the magnetohydrodynamic (MHD) flow, called the stagnation surface (Vincent & Lebohec 2010;Broderick & Tchekhovskoy 2015;Aharonian et al 2017), or near to the inner light surface of the magnetosphere (Crinquand et al 2020). Timedependent one-dimensional, general relativistic MHD simulations by Levinson & Segev (2017), Levinson & Cerutti (2018), Chen et al (2018), and Chen & Yuan (2020) and two-dimensional simulations by Crinquand et al (2020, for computational reasons, the latter authors had to restrict themselves to unrealistic parameters, however) have recently found inherently non-stationary gap solutions. Levinson & Cerutti (2018) and Kisaka et al (2020) indicate that the gap activity relaxes to low-amplitude quasi-steady oscillations after an initial spark event, while Chen et al (2018) and Chen & Yuan (2020) find cyclically enduring gap activity.…”
Section: Introductionmentioning
confidence: 99%
“…Particle acceleration by the gap electric field then gives rise to copious pair creation through the interaction of particles accelerated in the gap with soft photons emitted by the accretion flow. Recent one-dimensional (1D) general relativistic Particle-in-Cell (GRPIC) simulations of local spark gaps (Levinson & Cerutti 2018;Chen & Yuan 2020;Kisaka et al 2020) and global 2D GRPIC simulations of active Kerr BH magnetospheres (Parfrey et al 2019;Crinquand et al 2020Crinquand et al , 2021 indicate that the spark process is highly intermittent, conceivably inherently cyclic under certain conditions. However, the amplitude of the variations and the overall luminosity were found to depend rather sensitively on the pair creation opacity contributed by the soft radiation emitted from the surrounding accretion flow.…”
Section: Introductionmentioning
confidence: 99%